STRATEGI GURU DALAM MENERAPKAN ASESMEN FORMATIF DAN SUMATIF PADA PEMBELAJARAN DI KELAS KURIKULUM MERDEKA - Amalia Hasanah; Syahidah Putri, Alfianti; Heny Narendrany Hidayati (As-Sulthan Journal of Education, 2026)
This study focuses on teachers' implementation of the Merdeka Curriculum in classroom learning using formative assessment and summative assessment instruments with material scope in accordance with the Ministry of Primary and Secondary Education (Kemendikdasmen) academic year version. This study uses a literature study method with reference to case study results, teachers' problems needs presented in previous studies. These research limitations in teachers' implementation of the Merdeka Curriculum, which is adapted to the contextualisation of students' circumstances in subjects that require more attention to supporting aspects, and the influence of the government in the administration that teachers must carry out, thereby restrict innovative space to achieve learning objectives. Teachers' strategies in determining formative and summative assessments appropriate to students' circumstances still have obstacles, so continuous improvement of competence and technological guidance is needed in adapting to students' needs. In addition, teachers' creativity in strategy still needs to be developed, with flexibility being a point of opportunity for objective assessment results.